Understanding estimands - Nithya Jaideep Gogtay; Priya Ranganathan; Rakesh Aggarwal (Perspectives in Clinical Research, 2021)
Randomized controlled trials are the gold standard for determining the efficacy of a new intervention. Trials conducted for regulatory approval of an intervention compare the effect of the intervention with the standard of care or placebo to demonstrate efficacy. Randomization attempts to ensure that all known and unknown confounding factors are evenly distributed between the groups, and that the groups will be comparable at the end of the study, so that any inter-group differences in outcomes can be attributed to the intervention. However, in reality, intercurrent events may impact the assessment and subsequent interpretation of the outcome of interest. To address this, International Council for Harmonisation of Technical Requirements for Pharmaceuticals for Human Use (ICH) in 2017, released an addendum to the E9 guideline (ICH E9 R1) putting forth the concept of Estimands and Sensitivity Analysis in Clinical Trials. This addendum addresses how these intercurrent events are to be handled using the Estimand concept, which is now expected to be detailed in a separate section of the study protocol. In this paper, we discuss what estimands are, and their likely impact on how regulatory trial protocols and their statistical analyses plans are written and implemented. We also look at the application of the concept of estimands to routine clinical practice.